Straits Settlements Blue Book (imports/exports) 1903-1904 vol.42-43 (Great Britain : Public Record Office, 1971)
Mengandungi'Straits Settlements return of imports and exports for the year 1903';'Recapitulatory and comparative statement of the value of imports into and exports from the Colony of the Straits Settlements for the years 1902-1903';'Blue Book for the year 1904'.